MODEL PROGRAM PENINGKATAN MUTU GURU BERBASIS KEBUTUHAN - Andriyani, Dwi Esti (MAJALAH ILMIAH PEMBELAJARAN, 2011)
Teacher quality is one of important factors for good education. Therefore, it is a demand to develop and implement effective quality teacher improvement programs. Effective quality teacher improvement programs should be based on need assessments. This study aims to describe teacher quality improvement programs based on teachers' needs by studying: 1) the profile of Junior High School teachers in Banyumas which includes several teachers' aspects: their career rank, their academic qualification, and their mastery of teacher competencies; 2) teachers' opinions of teacher quality improvement programs, and 3) teacher quality improvement programs based on teacher needs. This is a survey research of 607 Junior High School teachers who were selected randomly. The research was conducted in Banyumas. The study employed opened and closed questionarries to collect data. The data analysis applied quantitative descriptive technique. The profile of Junior High School teachers in Banyumas show that none of teachers has been in IV/b career rank. However, most of teachers have met the academic qualification requirement. Only a few teachers hold Senior High School and D3 certificate and have irrelevant education background with the subjects that they teach. The teacher mastery of teacher competencies which are pedagogiec competency, professional competency, and scientific writing competency is fair. There are two programs needed to improve the quality of Junior High School teachers in Banyumas: 1) program to improve teacher's academic qualification, and 2) program to improve teacher's competency. Teacher academic qualification improvement program based on teachers' needs should consider following aspect; it should consist of undergraduate programs, D3 and S1, and graduate program: S2. 2) The study program should be in education field and relevant with the subjects that teachers teach. 3) The program should take place near or within location in which teachers live. 4) The program need to provide supports for teachers such as funding for studying – tuition fee and operational costs-, and study permit or dispensation to be free of or have only few teaching hours. Several aspects also should be considered in the implementation of teacher competency improvement program. According to teachers, training is the most suitable form to improve their competency besides workshop, seminar, and shortcourse (1-3 months). The programs should address a) teacher competency in subject matters which is needed by most of teachers, b) teacher competency in teaching, and also c) teacher competency in making a scientific writing. Implementing program in a location where teachers live in will be very helpful for teachers. Besides that, teachers need some supports such as money and also permit to join the program.